2018
DOI: 10.1371/journal.pone.0203810
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perception and practice towards oxytocin stability and quality: A qualitative study of stakeholders in three resource-limited countries

Abstract: BackgroundOxytocin is the gold standard drug for the prevention of postpartum haemorrhage, but limitations in cold chain systems in resource-constrained settings can severely compromise the quality of oxytocin product available in these environments. This study investigated the perspectives and practices of stakeholders in low and lower-middle income countries towards oxytocin, its storage requirements and associated barriers, and the quality of product available.MethodsQualitative inquiries were undertaken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 18 publications
5
50
0
4
Order By: Relevance
“…The data also indicate that oxytocin use is suboptimal with issues of availability and, potentially, potency. Unfortunately, in Bangladesh there is no formal guideline on the use and storage of oxytocin in the public and private sector [7,8]. The Directorate General of Health Services Bangladesh issued a circular in 2012 for the proper use of oxytocin in health facilities but this has not been institutionalized [5,9].…”
Section: Resultmentioning
confidence: 99%
“…The data also indicate that oxytocin use is suboptimal with issues of availability and, potentially, potency. Unfortunately, in Bangladesh there is no formal guideline on the use and storage of oxytocin in the public and private sector [7,8]. The Directorate General of Health Services Bangladesh issued a circular in 2012 for the proper use of oxytocin in health facilities but this has not been institutionalized [5,9].…”
Section: Resultmentioning
confidence: 99%
“…The analysis found evidence that Injectable Oxytocin (10 IU administered intramuscularly or intravenously) stands for the uterotonic of first choice for all births, but entails transport to be stored at temperature between 2 • C-8 • C. [38] A qualitative inquiry carried out in Ethiopia, India and Myanmar investigated the perspectives and practices of stakeholders towards oxytocin, the requirements for storage and barriers associated , as well as the quality of available product. [50] The study found that in Ethiopia, healthcare providers were aware that it is required that oxytocin should be kept refrigerated, and knew that the product is likely to lose its efficacy once not refrigerated. However, in Myanmar, it was noticed that Oxytocin was stored at room temperature in the labor wards in roughly thirty percent of the health facilities where data collection was conducted.…”
Section: 31mentioning
confidence: 99%
“…However, in Myanmar, it was noticed that Oxytocin was stored at room temperature in the labor wards in roughly thirty percent of the health facilities where data collection was conducted. [50] Similarly, in India knowledge of oxytocin storage requirements was shared among the health providers, and was frequently limited to medical doctors and obstetricians/gynecologists. The authors suggest to organize training targeting specific people and produce key advocacy messages emphasizing on the significance of cold chain storage to maintain the quality of oxytocin.…”
Section: 31mentioning
confidence: 99%
See 1 more Smart Citation
“…A WHO study of drug quality at central storage sites in such countries found that 64% of the oxytocin samples failed testing . A recent qualitative study in 3 lower‐resourced countries about the stability of oxytocin found low knowledge that oxytocin was heat sensitive, as well as difficulties maintaining required storage temperatures because of electricity and refrigeration issues …”
Section: Potential New Heat‐stable Drug For Prevention Of Postpartum mentioning
confidence: 99%